Family and Healthcare Decision Making: Implications for Bioethics in China - Marie C. Letendre, Joseph Tham, L.C. (Studia Bioethica, 2013)
For centuries, Chinese Confucian culture and the medical ethical tradition merged to form a single historical continuity, rich in content and great in character. However, to position Chinese Bioethics alongside the vigorous pace of the development of modern medicine, new content for cherished paradigms in family medical decision-making need to emerge. This paper discusses the contemporary implications for Chinese Bioethics in framing the commitments of the revered role of the family with current demands in healthcare decisions, often curtailed by competing medical or socio-political dimensions. The protective medical system in China relies on the prima facie presumption of familism directed towards the best interests of the patient. The 21st century practices of informed consent and truth-telling along with the financial sustainability of long term care present new complexities to a culture characterized by social harmony and communal values. Facing these bioethical issues and discerning their ambiguities will deepen Chinese Bioethics and advance the family’s decision-making role in healthcare.